(untitled) (European Science Methodical Journal, 2026)
Hepatocellular carcinoma (HCC) is one of the most common primary liver cancers in the world. Early diagnosis of HCC is difficult because symptoms often don’t appear until the tumor has spread and reached an advanced stage. Aminoacylase-1 (ACY1) is an enzyme belonging to the zinc-containing aminoacylase family. ACY1 is expressed in the liver, brain, kidneys, and some other tissues. ACY1 deficiency causes rare metabolic disorders that increase the excretion of N-acetylated amino acids in the urine. ACY1 is closely associated with HCC due to its active role in regulating metabolism and its influence on the growth and spread of cancer cells. ACY1 and its analogs are used as a biomarker for detecting tumors in cancerous tissues, as a potential therapeutic target, and as an inhibitor that prevents growth and spread in hepatocellular carcinoma. Aminoacylase-1 enzyme was purified from the serum of hepatocellular carcinoma patients. Ammonium sulfate (65%) was used for precipitation. Dialysis was performed to remove residual salts. The enzyme was isolated by ion exchange and gel filtration methods. A single isoform of the enzyme was obtained with a specific activity (94.36 U/mg) four times that of crude serum. The molecular weight of ACY1 was estimated by gel filtration and electrophoresis and was approximately (45000 Daltons). The kinetics and optimal conditions for the ACY1 enzyme were studied. The optimal substrate concentration was (7.5 mM), the value (Km=2.5 mM), the maximum velocity (Vmax=0.084 U/mL), the value (pH=7.5), the incubation period was (25 minutes), and the temperature was (37C°).